Applying Value Creation Framework to Offer Public Transport Improvement (Case from Trans Jogja and VÃ¤rmlandstrafik AB) - , NANDA KURNIAWAN; , Prof. Dr.-Ing. Ir. Ahmad Munawar, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Public Transportation in urban areas is expected to be main choice for peopleâs mobility. Public transport should solve the traffic problem and also meet the transportation needs of the community, safer and more comfortable. The aim of this thesis is apply value creation framework in public transportation based on S-D Logic, expect can offer public transportation improvement, and Trans Jogja from Yogyakarta Indonesia and VÃ¤rmlandstrafik AB Sweden be the case study for the application of value creation opportunity. The value creation framework consists of five dimensions along value creation opportunities occur. The dimensions include engaging customerâs emotional in the marketing activities, offering self-service options to customers, involving customers in staging customer experiences, solving customer problems, and getting customers involved in designing services. Then illustrates these concepts in a case of Trans Jogja BRT from Yogyakarta, Indonesia and VÃ¤rmlandstrafik AB from VÃ¤rmland, Sweden. This thesis use direct observation, interview and question to the related person/ firm as the primary data, and to support the result of interview use group discussion with the users. This research also use secondary data from some documentations, reports, journals, etc.This thesis ends up with conclusion and recommendation that aims to offer improvements for Trans Jogja and other public transport in Yogyakarta, Indonesia. Trans Jogja has many advantages if compared with other traditional city bus in Yogyakarta, and with these advantages Trans Jogja promoting a solution for urban transportation, and attract peoples to use public transport. And to do that Trans jogja has value creation opportunities which arise from applying value creation framework based S-D Logic. From the analysis and discussion it can be concluded that Trans Jogja little address the value creation based S-D Logic compared with VÃ¤rmlandstrafik AB. VÃ¤rmlandstrafik AB is address the value creation service and opportunity more than Trans Jogja. From conclusion, the need of applying value creation framework in Trans Jogja is to offer public transport improvement, especially in Yogyakarta as has been illustrated by Trans Jogja. Although the achievement of value creation opportunities are not as high as that achieved by VÃ¤rmlandstrafik AB, but Trans Jogja should learn from VÃ¤rmlandstrafik AB about what needs should be improved, so it can be an example of improvement to other public transportation